2015
DOI: 10.1523/jneurosci.2552-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

Tau-Dependent Kv4.2 Depletion and Dendritic Hyperexcitability in a Mouse Model of Alzheimer's Disease

Abstract: Neuronal hyperexcitability occurs early in the pathogenesis of Alzheimer's disease (AD) and contributes to network dysfunction in AD patients. In other disorders with neuronal hyperexcitability, dysfunction in the dendrites often contributes, but dendritic excitability has not been directly examined in AD models. We used dendritic patch-clamp recordings to measure dendritic excitability in the CA1 region of the hippocampus. We found that dendrites, more so than somata, of hippocampal neurons were hyperexcitabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
136
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(148 citation statements)
references
References 53 publications
(12 reference statements)
7
136
0
Order By: Relevance
“…While the first models used transgene-mediated expression of human amyloid precursor protein (APP) to model aspects of AD, other models followed to reflect tauopathies by transgenic expression of tau, ALS by expression of TDP-43, SOD1 or more recently through transgenic expansion of C9orf72 repeats. Neuronal network aberrations and hyperexcitability have been described for transgenic mouse models using EEG 91 and imaging. 92 Interestingly, network aberrations and hypersynchronous discharges and hyperexcitability 91 are detectable in APP mice preceding notable β-amyloid deposition 93 , and cognitive deficits in APP transgenic mice are apparent at early stages.…”
Section: Use Of Mouse Models To Map Networkmentioning
confidence: 99%
“…While the first models used transgene-mediated expression of human amyloid precursor protein (APP) to model aspects of AD, other models followed to reflect tauopathies by transgenic expression of tau, ALS by expression of TDP-43, SOD1 or more recently through transgenic expansion of C9orf72 repeats. Neuronal network aberrations and hyperexcitability have been described for transgenic mouse models using EEG 91 and imaging. 92 Interestingly, network aberrations and hypersynchronous discharges and hyperexcitability 91 are detectable in APP mice preceding notable β-amyloid deposition 93 , and cognitive deficits in APP transgenic mice are apparent at early stages.…”
Section: Use Of Mouse Models To Map Networkmentioning
confidence: 99%
“…Emerging findings suggest that dysregulation of neuronal network activity precedes and may contribute mechanistically to the degeneration of neurons in vulnerable brain regions in AD (Hall et al, 2015; Palop et al, 2007). In addition to increased incidence of seizures in AD patients (Vossel et al, 2017), a recent study revealed subclinical hippocampal seizures and spikes during sleep in AD patients (Lam et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Early studies showed that aggregating Aβ can increase neuronal vulnerability to excitotoxicity by inducing membrane lipid peroxidation which, in turn, impairs the function of membrane ion-motive ATPases (Na + /K + -ATPase and Ca 2+ -ATPase) and the neuronal glucose transporter GLUT3 (Mark et al, 1995a,b; Keller et al, 1997). Aβ and tau may also increase neuronal excitability by impairing K + channel function (Hall et al, 2015). Tau may itself contribute to abnormal neuronal excitability because genetic deletion or knockdown of tau can protect neurons against excitotoxicity (DeVos et al, 2013; Holth et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, tau reduction protected both wild-type and APP transgenic mice from excitotoxic insult [167]. Subsequent studies suggested tau involvement in mediating Aβ-induced changes in synaptic function [168], with tau reduction leading to lower epileptiform activity in APP transgenic mice [169] that may be linked to the Kv4.2 potassium channel [170]. More recently, it has been demonstrated that a reduction of endogenous tau using anti-sense oligonucleotides (ASO) delivered via intracerebroventricular infusion attenuated chemically-induced seizures in wild-type mice without other obvious detrimental cognitive effects after 1.5 months of treatment [171].…”
Section: Modulating Tau Expressionmentioning
confidence: 99%